Accounting Conservatism and National Culture - Pollyanna Gracy Wronski; Roberto Carlos Klann (BBR: Brazilian Business Review)
The following study intends to evaluate the influence of Hofstede’s cultural dimension (2017) on a corporation from several countries’ accounting conservatism scale. Based on Thomson Reuters’ data and a final sample of 54,484 observations (32 countries), the analysis was made over a period from 2010 to 2016 and was based off on Ball and Shivakumar’s work (2005) in measuring accounting conservatism. When analyzing each cultural dimension individually, it was noted that companies from countries that have an individualistic culture would engage in bad accounting conservatism, while companies with a long term orientation exhibited the opposite attitude, according to the survey’s scenario. In general, the conclusion is that the national culture can impact accounting information quality, impacting on a larger or lesser extent for accounting conservatism. One of the main contributions of this study is the comprehension that the intrinsic cultural factors of each nation can influence the quality of the accounting information.